Analisis Ketelitian Horizontal Pengukuran Orthofoto Menggunakan DJI Mavic 3 Enterprise Metode RTK dan PPK - Ary Pratama Putra; Fajrin Fajrin; Dwi Arini (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Aerial photo measurement aims to provide a real, fast, and interactive representation of the Earth's surface. Various methods of aerial photo acquisition and correction can be applied to obtain accurate results. The primary objective is to produce photos that present reliable and precise information consistent with actual conditions. A commonly used method in aerial photo mapping is the utilization of unmanned aerial vehicles (UAVs). The correction methods applied include direct correction, known as the Real-Time Kinematic (RTK) method, and post-processed correction, known as the Post-Processed Kinematic (PPK) method. This study aims to identify the highest horizontal orthophoto quality based on the Indonesian Geospatial Information Agency Regulation (BIG) No. 6 of 2018 concerning RBI map accuracy, by comparing the RTK and PPK methods, as well as variations in flight altitude during UAV data acquisition. The research conducted in Lemo II Village, Teweh Tengah District, North Barito Regency, Central Kalimantan Province revealed that the highest horizontal orthophoto quality was achieved using the PPK correction method at a flight altitude of 120 meters, with a horizontal RMSE value of 0.048 meters and an accuracy of 0.073 meters, which meets Class 1 standards at a 1:1000 scale. These values were obtained from tests conducted on 15 ICP points. Additional tests performed to determine the significance of model and method differences indicated that variations in flight altitude and photo correction methods have a significant impact on horizontal orthophoto quality.